2001
DOI: 10.1038/sj.neo.7900186
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A, VEGF-C, and VEGF-D in Colorectal Cancer Progression

Abstract: We aimed to assess the relationship of the angiogenic cytokines VEGF-A, VEGF-C, and VEGF-D and their receptors VEGFR-2 and VEGFR-3 in the adenoma-carcinoma sequence and in metastatic spread of colorectal cancer (CRC). mRNA expression levels were measured using semi-quantitative reverse transcription polymerase chain reaction in 70 CRC (35 with paired mucosae) and 20 adenomatous polyps. Immunohistochemistry and ELISA assessed protein expression. VEGF-D mRNA expression was significantly lower in both polyps and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
5
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(139 citation statements)
references
References 33 publications
11
119
5
4
Order By: Relevance
“…Patterns of VEGF-C mRNA expression were similar in the primary tumour and lymphatic metastases. The mRNA findings of the study were confirmed by immunohistochemistry, which showed no correlation between positive staining for VEGF-A, VEGF-C or VEGF-D and lymphatic spread (George et al, 2001). Further analyses of VEGF family mRNA levels in the adenoma -carcinoma sequence showed that of VEGF-A, VEGF-B and VEGF-C, only VEGF-A mRNA levels were consistently raised in invasive malignancy and this became apparent early on in disease progression, as levels were elevated to a similar extent in tumours with and without lymph node metastases or distant spread (Andre et al, 2000).…”
Section: Colorectal Cancermentioning
confidence: 63%
See 2 more Smart Citations
“…Patterns of VEGF-C mRNA expression were similar in the primary tumour and lymphatic metastases. The mRNA findings of the study were confirmed by immunohistochemistry, which showed no correlation between positive staining for VEGF-A, VEGF-C or VEGF-D and lymphatic spread (George et al, 2001). Further analyses of VEGF family mRNA levels in the adenoma -carcinoma sequence showed that of VEGF-A, VEGF-B and VEGF-C, only VEGF-A mRNA levels were consistently raised in invasive malignancy and this became apparent early on in disease progression, as levels were elevated to a similar extent in tumours with and without lymph node metastases or distant spread (Andre et al, 2000).…”
Section: Colorectal Cancermentioning
confidence: 63%
“…Tumour expression, assessed by RT-PCR, of VEGF-D mRNA was less than in normal tissue (George et al, 2001), while White et al (2002) found higher levels of VEGF-D protein expression in cancers detected by immunohistochemistry. The increased VEGF-D protein levels detected were associated with lymph node involvement and reduced overall and disease-free survival (White et al, 2002).…”
Section: Colorectal Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…VEGF-A is previously known to act as a specific blood angiogenic factor. However, recent studies have shown that VEGF-A plays a principle role in tumor progression and lymphatic metastasis (19,20). Here, we used RNAi to downregulate directly the expression of CD147 in Hepa1-6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…93,94 Although a number of reports show a positive correlation between VEGF-C and VEGF-D over expression and lymph node metastases in CRCs, [61][62][63][64][65][66]70,71 other studies do not show such relationships. [95][96][97] However, based on strong experimental studies showing a positive correlation between VEGF-C or VEGF-D expression with lymph node metastases (see Table I), it seems clear that both VEGF-C and VEGF-D may contribute to the disease course in CRC.…”
Section: Molecular Mediators Of Lymphangiogenesismentioning
confidence: 99%